Cross-Talk Between Butyric Acid and Gut Microbiota in Ulcerative Colitis Following Fecal Microbiota Transplantation - Xu, Hao-Ming; Huang, Hong-Li; Xu, Jing; He, Jie; Zhao, Chong; Peng, Yao; Zhao, Hai-Lan; Huang, Wen-Qi; Cao, Chuang-Yu; Zhou, Yong-Jian; Zhou, You-Lian; Nie, Yu-Qiang (Frontiers in Microbiology, 2021)
Fecal microbiota transplantation (FMT) can inhibit the progression of ulcerative colitis (UC). However, how FMT modulates gut microbiota and which biomarker is valuable for evaluating the efficacy of FMT have not been clarified. This study aimed to determine the changes in gut microbiota and their relationship with butyric acid following FMT for UC. Fecal microbiota (FM) was isolated from healthy individuals or mice and transplanted into 12 UC patients or colitis mice induced by DSS. Their clinical colitis severities were monitored. Their gut microbiota were analyzed by 16S sequencing and bioinformatics. The levels of fecal short-chain fatty acids (SCFAs) from 5 UC patients with recurrent symptoms after FMT and individual mice were quantified by LC-MS. The impact of butyric acid on the abundance and diversity of gut microbiota was tested in vitro. The effect of combination of butyric acid-producing bacterium and FMT on clinical responses of 45 UC patients was retrospectively analyzed. Compared with that in the controls, the FMT significantly increased the abundance of butyric acid-producing bacteria and fecal butyric acid levels in UC patients. The FMT significantly increased the α-diversity, changed gut microbial structure and elevated fecal butyric acid levels in colitis mice. Anaerobic culture with butyrate significantly increased the α-diversity of gut microbiota from colitis mice and changed their structure. FMT combination with Clostridium butyricum-containing probiotics significantly prolonged the UC remission in clinic. Therefore, fecal butyric acid level may be a biomarker for evaluating the efficacy of FMT for UC and addition of butyrate-producing bacteria may prolong the therapeutic effect of FMT on UC by changing gut microbiota.